Optimization of upland rice yields inoculated with Azotobacter, Agrobacterium tumefaciens, and Mycorrhizae through humic acid and micro-Fertilizer provision in Coastal Land - Bertham, Y. H.; Nusantara, A. D.; Barchia, F.; Simarmata, M. (International Journal of Agricultural Technology, 2024)
The result showed that the treatment combination of 16 L ha-1 humic acid and 140 g ha-1 micro-fertilizer produced the heaviest grain weight of 4.03 kg plot-1 or an equivalent of 7.16 tons ha-1. Yield was higher than the average upland rice production of the Inpago 10 variety, i.e. 4.0 tons ha-1 and it reached 98.08% of the potential yield of 7.30 tons ha-1. The best dose of humic acid was 16 L ha-1 which produced the highest grain weight per plant, pH-KCl, plant tissue N and P content, and seed Zn and Fe. Furthermore, the best dose of micro-fertilizer was 140 g ha-1 which generated the greatest number of paddy grains per panicle and grain weight per plant, as well as the highest P content in the tissue, and Cu, Zn, Mn, and Fe in seeds.